Corticolous myxobiota of Terminalia catappa L. (Combretaceae) - Bezerra, Andrea Carla Caldas; Cavalcanti, Laise de Holanda (SITIENTIBUS série Ciências Biológicas, 2007)
Studies were carried out on the corticolous myxobiota of Terminalia catappa L. (Combretaceae) found under different environmental conditions in Olinda and Recife counties, in Pernambuco State, Brazil. Out of total of 237 specimens (field and moist-chamber) ten species belonging to five families and six genera were identified: Licea castanea G. Lister, L. denudescens H.W. Keller & T.E. Brooks, L. pedicellata (H.C. Gilbert) H.C. Gilbert (Liceaceae); Cribraria violacea Rex (Cribrariaceae); Perichaena chrysosperma (Curr.) Lister, P. depressa Libert, P. vermicularis (Schwein.) Rostaf. (Trichiaceae); Physarum auriscalpium Cooke, P. crateriforme Petch. (Physaraceae); Diderma aff. chondrioderma (de Bary & Rostaf.) G. Lister (Didymiaceae). Results suggest that the myxomycete community composition among the two studied areas were similar (CC=0.88). Descriptions, comments and geographical distribution in Brazil of each species are presented.